Fenomen piosenki francuskiej w Polsce, czyli Piaf wiecznie żywa - Joanna Warmuzińska‑Rogóż (Ksiegarnia Akademicka Publishing, 2021)
The fans of French songs have recently received a real windfall: two CDs prepared by Michał Bajor with the French songs chosen by the artist. Polish translations by Wojciech Młynarski, very accurate at the level of meaning, are an important advantage of the publication. However, the high fidelity between the original and the translation does not provide the excellent compatibility between both groups of texts. This article shows, from the point of view of the process of translation, the functioning of the songs selected by the authors of the disc both in the target and original culture. While in France many of the songs selected by Michał Bajor are considered as classics that have no longer a special interest among the French auditors, on a contrary in the Polish culture it is possible to observe the enduring interest in this form of creation. Interestingly, we find that the average Polish recipient perceives the song from the perspective of artists such as Edith Piaf, Charles Aznavour and Joe Dassin, without being aware of new trends in music. We are therefore faced with an interesting cultural transfer process, in which the faithful translation does not guarantee the absence of deformation, resulting in this case, at least in part, from differences in the “time‑space” of the original and the translation.